Civil Society: The Concept and Its Historicisation - Kučera, Rudolf (Dějiny – teorie – kritika, 2007)
This study is devoted to the ways the concept of civil society may be used in Czech historiography. It analyses the conceptualisation of the term in Czech historical research over the last forty years and makes reference to certain significant ambiguities associated with the term civil society. The use of the term civil society in Czech historiography is still oriented predominantly toward the German concepts of the 1980s and ‘90s – that is, toward an understanding of civil society as a certain form of society-wide organisation. The author argues against this conception and proposes that civil society should be grasped not as a certain form of social organisation, but rather as a specific pattern of conduct, or perhaps even as a specific social sector. In the context of current debates in the Anglo-Saxon and German-language spheres, he then presents several basic ways of defining civil society and sketches out possible fresh uses of the concept of civil society for historical analysis.